Momentum in tennis: Controlling the match - Dietl, H. M.; Nesseler, C. (International Journal of Sport Psychology, 2017)
Although many studies examine if players in sports and especially in tennis benefit from a psychological or physiological boost (momentum) none examine whether the set score as a dependent variable or tournament rounds as independent variables are important determinants when assessing momentum. We empirically investigate whether professional female and male tennis players benefit from momentum. In contrast to previous work, we find players benefit from momentum as long as they control a match. Once players lose control over a match, they have a significantly lower chance to win the next set than their opponent. This loss of control results in what we call anti-momentum.